WALI NIKAH DALAM FIQH DAN PENERAPANNYA DALAM UNDANG-UNDANG KELUARGA ISLAM BRUNEI (PINDAAN 2012) - Pehin Datu Seri Maharaja, Nurol Huda binti (Universitas Islam Negeri Raden Fatah Palembang, 2017)
Guardians are an important component in the ceremony ofmarriage for Muslim. The objective of article is to review the status of aguardian in determining the validity of a marriage, explaining the typeof guardians and conditions that need to be present. In addition, thestudy also wanted to explain the requirement of the guardian's permittin marriage under the Brunei Islamic Family Law (Pindaan 2012). Theanalys of this article will expose the opinions in the four models of fiqhalong with their proofs rather than the source of the Qur'an, theSunnah and so on. The next review will review the implementation ofthe fiqh within the Brunei Family Law. The study will also examinethe aspects of equality and disagreements in the four sects andallotments in the law. The result of the study found that the guardianis the determinant of marriage validity according to the jumhur ulamaand Syara 'Law derived from the Syafi'i fiqh.